Air pollution emission from the copper smelter Complex Bor in Serbia - Andjela B Stanojevic (Annals of Environmental Science and Toxicology - Peertechz Publications, 2021)
Ever since the industrial revolution, air got significantly polluted by the industry. Air pollution is even more concentrated in cities that have an industrial zone. Especially in these zones, the presence of Sulfur-dioxide (SO2) and suspended Particles (PM) in the air is very high. Prolonged exposure to SO2 and PM can cause cancer, cardiovascular and respiratory disorders in humans. The aim of this paper was to a review available literature on air pollution by sulfur dioxide and suspended particles in the air region of Bor Copper complex, as well as to determine whether the investigated results are contradictory. Studies from prior years (2004-2015), as well as 2019, indicate rise of SO2 and PM air pollutants in the atmosphere in the region of the copper smelter of the Bor Complex in Serbia, which can cause serious consequences for human well-being. However, the results of research by different authors for the same years are not in agreement, with that said, a review of the literature indicates significant differences. In addition, no continuous research on any air pollutants has been done for several consecutive years. This can be an interesting question for the scientific public in Serbia. Review of available literature indicates that in Serbia, solving this problem must be taken more seriously.